2021
DOI: 10.1111/inr.12732
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID19 on advanced practice nursing education and practice: A qualitative study

Abstract: Aim: To explore Master of Nursing students' perspectives toward the impact of coronavirus disease 2019 (COVID-19) on the advanced practice nurse preparatory education and practice. Background: Like many nursing education programmes, the advanced practice nurse preparatory training was greatly affected and had to radically change to adapt to the disruptions caused by the pandemic. The COVID-19 pandemic has created a strain on the healthcare system and advanced practice nurses have been expected to modify their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…The pre-rejected mean quality score was 26.73 (95% CI = 24.74–28.72). In the end, only 23 articles, the majority of which were published during the pre-COVID-19 pandemic [ 52 66 ] and the remaining [ 67 – 74 ] during the COVID-19 period, were included, with the final mean quality score of 29.78 (95% CI = 28.34–31.22). For the mixed-method study, only the qualitative section was evaluated and extracted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pre-rejected mean quality score was 26.73 (95% CI = 24.74–28.72). In the end, only 23 articles, the majority of which were published during the pre-COVID-19 pandemic [ 52 66 ] and the remaining [ 67 – 74 ] during the COVID-19 period, were included, with the final mean quality score of 29.78 (95% CI = 28.34–31.22). For the mixed-method study, only the qualitative section was evaluated and extracted.…”
Section: Resultsmentioning
confidence: 99%
“…However, the COVID-19 studies explored the learners’ experiences on how technology becomes a part of daily life, focusing on life experiences rather than on technology. It can be summarized where the pre-COVID studies observed consumer and design studies on the use of technology [ 54 – 66 ], except for some [ 52 , 53 ], whereas COVID-19 studies observed life experience as learners utilizing technology in learning [ 67 , 69 , 71 , 72 , 74 ], except for some [ 68 , 70 , 73 ]. Studies focusing on the technology and product emphasized their advantages and were optimistically reported, whereas studies on life experience paid more attention to reporting on the challenges and limitations in learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen students were interviewed for this descriptive, qualitative study. Key themes found included the concept of “overcoming adversity through innovation” and “acceptance of remote learning” ( Woo et al, 2021 ). Even with differences in educational systems and interview questions, the Singapore results aligned with aspects of this research, in that flexibility and innovation were noted by both studies to be key concepts in students adapting to the changes in graduate nursing education due to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As of February 15, 2022, there have been over 413 million diagnosed cases worldwide and over 5.8 million deaths, according to the Coronavirus Resource Center ( John Hopkins University and Medicine, 2022 ). Despite an increase in persons being vaccinated, the surge in infections attributed to new variants is evidence that the coronavirus continues to be a worldwide health crisis ( World Health Organization, 2022 ).…”
Section: Introductionmentioning
confidence: 99%